IMPLEMENTASI STRATEGI POJOK BACA DALAM MENINGKATKAN MINAT LITERASI SISWA SEKOLAH DASAR - Rista; Haifaturrahmah; Sukron Fujiaturrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to provide an in-depth description of the implementation of the reading corner strategy in fostering literacy interest among elementary school students. A reading corner serves as a supporting program of the School Literacy Movement designed to create a literacy-friendly learning environment. This research employed a descriptive qualitative approach involving a classroom teacher and fourth-grade students as research subjects. Data were collected through observations of students’ reading activities in the reading corner, interviews with the teacher, and documentation of reading logs and book inventories. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The results of the study reveal that a creatively managed and consistently operated reading corner can enhance students’ literacy interest by providing diverse reading materials, a comfortable reading atmosphere, and active teacher involvement as a literacy facilitator. Furthermore, the reading corner encourages independent reading habits and improves students’ motivation to comprehend texts. This research confirms that the reading corner strategy is effective in developing school literacy culture when supported by adequate facilities and continuous teacher guidance. Keywords: Reading Corner, Literacy Interest, Literacy Culture, Elementary School